The effectiveness of a one-day workshop based on cognitive behavioral therapy interpretation bias and meta-Emotions of women with postpartum depressive disorder - Ghazanfari, Nasim; Khademi, Ali; Mahmoud Alilou, Majid; Etemadnia, Mahin; Dousti, Rita (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to investigate the effectiveness of a one-day workshop based on cognitive behavioral therapy of interpretation bias and hyperexcitability in patients with postpartum depression. Methods: It was a quasi-experimental research design of pre-test, post-test and follow-up type with a control group. The statistical population of this study included all women with perinatal depression in Selmas city who were referred to health centers in 2021 to receive psychological services. The sample size includes 50 people (25 people in the experimental group and 25 people in the control group) from the statistical population were selected by available sampling method and divided into two control and experimental groups. For the experimental group, a one-day workshop based on cognitive behavioral therapy based on the Stark model (1996) was implemented, while the control group did not receive any training. The research tools included the Edinburgh Depression Questionnaire by Cox et al. (1996), the Ambiguous Scenarios Test for Depression by Brena et al. The data was analyzed using descriptive statistics and analysis of variance test with repeated measurements. Results: The results showed that the one-day workshop based on cognitive behavioral therapy on interpretation bias (F=258.60, P<0.001) and positive euphoria (F=120.70, P<0.001) and negative excitement (F=56.79, P<0.001) had a significant effect in the post-test and follow-up stages. Conclusion: The findings of this research provide useful information regarding a one-day workshop based on cognitive behavioral therapy, and counselors and psychologists can use this intervention to improve interpretation bias and hyper-excitement in postpartum depression.